Examining The Effects of Current Ratio, Earnings Per Share, And Debt-To-Equity Ratio on Stock Prices in The LQ45 Index - Luh Ketut Adnya Suari; I Wayan Widnyana; Gregorius Paulus Tahu (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Stock prices, defined as the value per share traded in the capital market, fluctuate in response to supply and demand. Higher stock prices indicate an increase in a company’s value, and vice versa. Stock prices can also reflect a company’s performance, which moves in tandem with its financial results. This study examines financial ratios that influence stock prices, specifically the Current Ratio, Earnings Per Share, and Debt-to-Equity Ratio. This study aims to test and obtain empirical evidence regarding the influence of the Current Ratio, Earnings Per Share, and Debt-to-Equity Ratio on the stock prices of companies listed on the LQ45 index at the Indonesia Stock Exchange. The study population consists of all LQ45 index companies listed on the Indonesia Stock Exchange for the period 2021–2023. The sample was determined using purposive sampling, resulting in 20 companies listed on the LQ45 index on the Indonesia Stock Exchange, yielding a total of 60 data observations during the study period. The data used were quantitative data obtained from , www.idx.co.id, and . Data analysis was performed using multiple linear regression. The results indicate that the Current Ratio and Earnings Per Share have a positive effect on stock prices for companies listed on the LQ45 index, while the Debt-to-Equity Ratio has a negative and significant effect on stock prices for companies listed on the LQ45 index.